Oxidant/Antioxidant Equilibrium and Neurotransmitter Levels in Camelids Used for Circus Activities: A Preliminary Study - Raffaella Cocco; Federica Arrigo; Sara Sechi; Maria Rizzo; Giuseppe Piccione; Francesca Arfuso (Veterinary Sciences, 2025)
The conditions of animals in captivity have long been a cause for concern, and for that reason should be carefully assessed. In circus activities, animals are used for different purposes, but their needs are different due to their physiological peculiarities. The aim of the present study was to investigate the emotional state and the oxidant/antioxidant equilibrium in dromedaries, camels, and llamas subjected to circus management. Blood samples were taken from five specimens of three different species in order to assess the serum concentrations of noradrenaline, dopamine, serotonin, and the plasma levels of reactive oxygen metabolites (d-Roms) and the animals’ biological antioxidant potential (BAP). The results showed higher levels of d-Roms in dromedaries and llamas than camels and higher concentrations of BAP in camels than other species. Finally, dromedaries showed a higher dopamine concentration than llamas. This preliminary study suggested that some of the species investigated here are more influenced by the circus environment, especially on a relational level. Although the results collected in this study are preliminary and need to be supported by further, more comprehensive investigations from the point of view of welfare assessment, it could be hypothesized that the emotional state and the oxidant/antioxidant balance is very important to assess in an environment such as the circus.